Law through the life course / Jonathan Herring. - Herring, Jonathan (Bristol University Press, 2021)
This book is the first to explore the interactions of the law with the life course in order to understand the complex life journey as a whole. Jonathan Herring reveals how the law privileges 'middle age' to the detriment of the whole life story and explains why an understanding of the life course is important for lawyers.